SUCCESS WITH ENGLISH: THREE WHO ACHIEVED IT AND WHAT WORKED FOR THEM - Hamed Barjesteh; Mohammad Bagher Khatibi (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2010)
Good language learner studies show that attending to form is associated with successful learning. This paper reports interviews with three university English majors who had been the best students in a talk show program and got a score band of 7 or beyond in IELTS. The interviewees regarded text memorization and imitation as the most effective methods of learning English. They had been initially forced to use these methods but gradually came to appreciate them. The practice enabled them to attend to and learn collocations and sequences, to borrow these sequences for productive use, to improve pronunciation, and to develop the habit of attending to details of language in the context of language input. The paper concludes that such practice enhances noticing and rehearsal and hence facilitates second language acquisition.